ANALISIS PERENCANAAN DAN EVALUASI ANGGARAN DALAM MENINGKATKAN KINERJA PADA KANTOR PELABUHAN PERIKANAN NUSANTARA SIBOLGA - Yohannes Gindo Roy Parulian Sinaga; Nur Ainun Hasibuan; Sriayu Aritha Panggabean (KOLONI, 2023)
This research was conducted at Sibolga Fishing Port. The purpose of this study is to determine whether there is an effect of Budget Planning and Budget Evaluation on Financial Performance at Sibolga Fishing Port. The research method used is a quantitative method. The population in this study is the financial statement of 2019– 2021. The sampling technique in this study uses Nonprobability sampling: Saturated Sampling.This research uses quantitative descriptive method and data analysis method uses multiple regression analysis with hypothesis testing using t test and f test. Based on the results of the t test, it was found that the factors of Budget Planning and Budget Evaluation each had a significant effect on FinancialPerformance. Through the f test, it was found that Budget Planning and Budget Evaluationtogether had a positive effect on Business Perfor FinancialPerformance mance for Sibolga Fishing Port. The results of the coefficient of determination obtained a value of 81,80%. And the multiple linear regression test Y = 2,9496+ 0,247X1 + 0,139X2 it can be assumed that if the Budget Planning has increased by one-unit (%), then Financial Performance will decrease with a value of 0,24%, and if the Budget Evaluation has increased by one-unit (%) then Financial Performance will experience an increase with a value of 0,139%. Keywords: Budget Planning, Budget Evaluation, andFinancial Performance